Autoantibody Signature In Chronic Viral Hepatitis C And B (Journal of Pharmaceutical Negative Results, 2023)
Background: Testing for liver-related autoantibodies should be included in the workup of patients with hepatitis or cholestasis of unknown origin. Although most of these autoantibodies are not disease specific, their determination is a prerequisite to diagnose autoimmune hepatitis (AIH) and primary biliary cholangitis (PBC), and they are components of the diagnostic scoring system in these diseases. Chronic hepatitis C represents an important cause of morbidity and mortality because of it is widespread prevalence. liver involvement is only one side of the coin, as extra hepatic manifestations may complicate the course of the disease in over 70% of hepatitis C virus (HCV) infected individuals. Antibodies are a vital part of the immune response for recognition and elimination of invading organisms. However, when the immune system is dysfunctional, it can develop antibodies that react to self. The development of autoantibodies (auto-Abs) generally occurs during auto-immune disease, but their induction can also be a consequence of a chronic infection in susceptible individuals